Investigation of snow characteristics in the microwave range for avalanche forecasting - Kadyrakunov, K.B.; Nikulin, V.E.; Nurmagambetova А.K.; Aizhanova, A.E.; Nurgalieva, R.T. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
It should be noted that avalanches of accumulated snow masses are typically triggered by climatic factors, including abrupt weather changes (such as variations in atmospheric pressure and air humidity), precipitation, and heavy snowfall. The volume of snow in an avalanche can reach several million cubic meters. However, even avalanches with a volume of about 5 m³ can be life-threatening. To reduce and prevent these negative factors, it is necessary to predict and prevent the occurrence of avalanches at an earlier stage. This task is solved by regular monitoring of snow and weather conditions on the proposed area of mountain slopes. In order to achieve this objective, a variety of methods and techniques based on different physical and technical principles are currently used. One of the most promising directions is the use of radio waves of ultra-high frequency (UHF) range. The present study is devoted to the examination of the possibility of UHF methods for the remote measurement of snow parameters. Two experimental installations for measurement of various snow parameters in the microwave radio wave range have been constructed for avalanche forecasting. Predictors of avalanches are chosen based on physical considerations and methods of mathematical statistics. The objective of our research is to create an installation to study the characteristics of mountain snow in the avalanche-hazardous areas of the Shimbulak ski resort. The main parameters of electric snow that influence the process of transmission, propagation and reflection of radio waves are considered. As a result of the changes, the dipole moment increases, which causes the separation band of the alternating influence of water to expand and move to the low-frequency region. The results of experimental studies of radio-wave attenuation in snow used to calculate the absorption coefficient of microwave radiation in snow are presented. Dielectric permeability and tangent of the angle of snow losses have been measured using the waveguide method.